Investigation of scutellarin’s mechanism in inhibiting colon cancer cells through molecular docking analysis - Chuc Nguyen Thanh; Hoa Tong Thi Thu; Tung Bui Thanh (Vietnam Journal of Science, Technology and Engineering)
Colon cancer, also referred to as colorectal cancer when involving both the colon and rectum, originates in the large intestine. Alongside conventional treatments, targeted therapy has garnered increasing attention. The wnt/β-catenin pathway is one of the therapeutic targets under investigation for colon cancer. Scutellarin, a bioactive compound, has demonstrated efficacy in cancer treatment across numerous studies. This study evaluates the impact of scutellarin on three key targets within the wnt/β-catenin pathway using molecular docking techniques and analyses its drug- likeness characteristics, pharmacokinetics, and toxicity parameters. Results indicate that scutellarin inhibits the wnt/β-catenin pathway, evidenced by its significantly low binding energy values with three proteins: catenin beta-1, glycogen synthase kinase-3 beta, and casein kinase I isoform delta. Pharmacokinetic predictions suggest scutellarin exhibits poor intestinal absorption, good tissue distribution, does not cross the blood-brain barrier, is metabolised in the liver, excreted via the kidneys, and displays no toxicity. Lipinski’s rule analysis confirms that scutellarin possesses drug-like properties. Consequently, further in vitro and in vivo studies are warranted to comprehensively evaluate its potential in colon cancer treatment.